Теплообмін шахових пакетів гвинтоподібних труб з рівнорозвиненою поверхнею в умовах природної тяги - Баранюк, Олександр Володимирович; Рачинський, Артур Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Проведено дослідження структури течії та теплообміну в шахових пакетах гвинтоподібних труб з рівнорозвиненою поверхнею в умовах природної тяги засобами CFD-моделювання. Отримані числові розподіли швидкостей і температур поблизу поверхні труб та в сліді за ними, які дають змогу розробити узагальнюючі розрахункові залежності для визначення середнього теплообміну в пакетах таких труб. Результати досліджень можуть бути використані для модернізації методик розрахунку теплообміну апаратів повітряного охолодження.

Helical pipes with similar developed surface patterns efficiently operate under forced convection conditions. The available literature describes their essential advantages over the tubes of a round-ribbed profile and the possibility of their application as a heat-exchanging section for the air-cooling unit. However, the peculiarities of the operation of such units require checking an opportunity for the use of helical pipes with similar developed surface patterns under natural draft conditions. The purpose of the research is to get new data on the flow structure in the intertube space of the staggered banks of such pipes under natural draft conditions. These data are required for the in-depth analysis of the appropriateness of the use of such pipes for “dry” air cooling systems. The methods of investigation included the use of the academic licensed software package ANSYS Student for numerical computations. It was established that the heat exchange in ribbed pipes under natu-ral draft conditions is specified first of all by the parameters of the staggered bank (longitudinal and transversal pitches of the arrangement of pipes in the bank) and the geometric parameters of the pipes, in particular the pitch between the humps and the dents on the tube surface that form its helical surface. Design ratios were suggested for the determination of the averaged heat exchange in the staggered banks of the sin-gle-thread helical pipes with similar developed surface patterns. It was shown that the pitch characteristics of the banks have the greatest effect on the similarity equation. A preliminary validation was carried out for the methods adopted for the design of helical pipes and the known methods used for the computation of the staggered banks of smooth cylindrical pipes. The obtained research data can be used for the evaluation of the intensification of the heat exchange and for the flow analysis in order to increase the efficiency of the heat-exchange equipment.
Heat exchange in staggered threaded pipe banks with similar developed surface patterns under natural draft conditions
Keywords: шаховий пучок; природна тяга; моделювання; staggered bank; natural draft; the simulation